Barriers to COVID-19 vaccination among older adults in Mexico City - Pablo Gaitán-Rossi; Miranda Mendez-Rosenzweig; Erika García-Alberto; Mireya Vilar-Compte (BMC, 2022)
Abstract Vaccines are effective to reduce COVID-19 related outcomes, but universal vaccination campaigns can reveal within-country access inequities. Mexico City has had high rates of COVID-19 related morbidity and mortality and a population survey warned that vaccine acceptance was lowest in older adults. Since February 2021, Mexico started a universal and free vaccination campaign prioritizing older adults. By April 17, every older adult in Mexico City had been eligible to receive the first dose. A week later, we conducted a telephone survey representative of older adults residing in Mexico City (n = 503). We asked if they received their first dose and, if they haven't, we followed-up with an open question to register their reasons. In addition to sociodemographic characteristics and food insecurity, we also inquired about vaccine hesitancy, health concerns related to COVID-19, self-rated health, comorbidities, frailty, and depression. The objective of the study was to identify the main barriers to receive the first dose of the vaccine. We estimated descriptive statistics and logistic regression models. Results show that 7.6% of older adults in Mexico City did not receive their first dose. Barriers for not receiving it were vaccine hesitancy (60.4%), not having COVID-19 health concerns (46.4%), poor self-rated health (46.7%), a previous diagnosis of depression (35.7%), low socioeconomic status (65.4%), and household food insecurity (59.8%). Responses to the open question clustered in four themes: misinformation about the process (30%), distrust of the vaccine (24%), personal health problems (24%), and difficulties to get an appointment (22%). Logistic regression models adjusted for vaccine hesitancy and revealed two distinct reasons for not having their first dose: 1) vaccine hesitancy and misinformation on COVID-19, and 2) household food insecurity. Reaching these two groups requires active and differentiated public-health measures; the first with additional information from trusted sources, and the second by facilitating vaccination in neighborhoods with high levels of food insecurity and informal labor, where missing a day's work is a strong disincentive. Vaccination campaigns need an equity lens to reach universal coverage; ensuring full access demands thorough and carefully tailored new interventions.